Mercurial > hg > Members > kono > Proof > category
comparison equalizer.agda @ 253:24e83b8b81be
fix
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Wed, 11 Sep 2013 20:26:48 +0900 |
parents | e0835b8dd51b |
children | 45b81fcb8a64 |
comparison
equal
deleted
inserted
replaced
252:e0835b8dd51b | 253:24e83b8b81be |
---|---|
27 ek=h : {d : Obj A} → ∀ {h : Hom A d a} → {eq : A [ A [ f o h ] ≈ A [ g o h ] ] } → A [ A [ e o k {d} h eq ] ≈ h ] | 27 ek=h : {d : Obj A} → ∀ {h : Hom A d a} → {eq : A [ A [ f o h ] ≈ A [ g o h ] ] } → A [ A [ e o k {d} h eq ] ≈ h ] |
28 uniqueness : {d : Obj A} → ∀ {h : Hom A d a} → {eq : A [ A [ f o h ] ≈ A [ g o h ] ] } → {k' : Hom A d c } → | 28 uniqueness : {d : Obj A} → ∀ {h : Hom A d a} → {eq : A [ A [ f o h ] ≈ A [ g o h ] ] } → {k' : Hom A d c } → |
29 A [ A [ e o k' ] ≈ h ] → A [ k {d} h eq ≈ k' ] | 29 A [ A [ e o k' ] ≈ h ] → A [ k {d} h eq ≈ k' ] |
30 equalizer : Hom A c a | 30 equalizer : Hom A c a |
31 equalizer = e | 31 equalizer = e |
32 | |
32 | 33 |
33 -- | 34 -- |
34 -- Burroni's Flat Equational Definition of Equalizer | 35 -- Burroni's Flat Equational Definition of Equalizer |
35 -- | 36 -- |
36 record Burroni { c₁ c₂ ℓ : Level} ( A : Category c₁ c₂ ℓ ) {c a b : Obj A} (f g : Hom A a b) (e : Hom A c a) : Set (ℓ ⊔ (c₁ ⊔ c₂)) where | 37 record Burroni { c₁ c₂ ℓ : Level} ( A : Category c₁ c₂ ℓ ) {c a b : Obj A} (f g : Hom A a b) (e : Hom A c a) : Set (ℓ ⊔ (c₁ ⊔ c₂)) where |
114 ≈↑⟨ assoc ⟩ | 115 ≈↑⟨ assoc ⟩ |
115 e o ( h-1 o ( h o k eqa j eq ) ) | 116 e o ( h-1 o ( h o k eqa j eq ) ) |
116 ≈⟨ cdr assoc ⟩ | 117 ≈⟨ cdr assoc ⟩ |
117 e o (( h-1 o h) o k eqa j eq ) | 118 e o (( h-1 o h) o k eqa j eq ) |
118 ≈⟨ cdr (car h-1h=1 ) ⟩ | 119 ≈⟨ cdr (car h-1h=1 ) ⟩ |
119 e o (id1 A c o k eqa j eq ) | 120 e o (id c o k eqa j eq ) |
120 ≈⟨ cdr idL ⟩ | 121 ≈⟨ cdr idL ⟩ |
121 e o k eqa j eq | 122 e o k eqa j eq |
122 ≈⟨ ek=h eqa ⟩ | 123 ≈⟨ ek=h eqa ⟩ |
123 j | 124 j |
124 ∎ | 125 ∎ |
137 ∎ )) ⟩ | 138 ∎ )) ⟩ |
138 h o ( h-1 o j ) | 139 h o ( h-1 o j ) |
139 ≈⟨ assoc ⟩ | 140 ≈⟨ assoc ⟩ |
140 (h o h-1 ) o j | 141 (h o h-1 ) o j |
141 ≈⟨ car hh-1=1 ⟩ | 142 ≈⟨ car hh-1=1 ⟩ |
142 id1 A c' o j | 143 id c' o j |
143 ≈⟨ idL ⟩ | 144 ≈⟨ idL ⟩ |
144 j | 145 j |
145 ∎ | 146 ∎ |
146 | 147 |
147 -------------------------------- | 148 -------------------------------- |
192 → ( keqa : Equalizer A (k eqa' e (fe=ge eqa)) (A [ f o e' ]) (A [ g o e' ]) ) | 193 → ( keqa : Equalizer A (k eqa' e (fe=ge eqa)) (A [ f o e' ]) (A [ g o e' ]) ) |
193 → A [ A [ e o c-iso-r eqa eqa' keqa ] ≈ e' ] | 194 → A [ A [ e o c-iso-r eqa eqa' keqa ] ≈ e' ] |
194 e'←e {c} {c'} {a} {b} {f} {g} {e} {e'} eqa eqa' keqa = let open ≈-Reasoning (A) in begin | 195 e'←e {c} {c'} {a} {b} {f} {g} {e} {e'} eqa eqa' keqa = let open ≈-Reasoning (A) in begin |
195 e o c-iso-r eqa eqa' keqa | 196 e o c-iso-r eqa eqa' keqa |
196 ≈⟨⟩ | 197 ≈⟨⟩ |
197 e o k keqa (id1 A c') ( f1=g1 (fe=ge eqa') (id1 A c') ) | 198 e o k keqa (id c') ( f1=g1 (fe=ge eqa') (id c') ) |
198 ≈↑⟨ car (ek=h eqa' ) ⟩ | 199 ≈↑⟨ car (ek=h eqa' ) ⟩ |
199 ( equalizer eqa' o k eqa' e (fe=ge eqa) ) o k keqa (id1 A c') ( f1=g1 (fe=ge eqa') (id1 A c') ) | 200 ( equalizer eqa' o k eqa' e (fe=ge eqa) ) o k keqa (id c') ( f1=g1 (fe=ge eqa') (id c') ) |
200 ≈⟨⟩ | 201 ≈⟨⟩ |
201 ( e' o k eqa' e (fe=ge eqa) ) o k keqa (id1 A c') ( f1=g1 (fe=ge eqa') (id1 A c') ) | 202 ( e' o k eqa' e (fe=ge eqa) ) o k keqa (id c') ( f1=g1 (fe=ge eqa') (id c') ) |
202 ≈↑⟨ assoc ⟩ | 203 ≈↑⟨ assoc ⟩ |
203 e' o (( k eqa' e (fe=ge eqa) ) o k keqa (id1 A c') ( f1=g1 (fe=ge eqa') (id1 A c') ) ) | 204 e' o (( k eqa' e (fe=ge eqa) ) o k keqa (id c') ( f1=g1 (fe=ge eqa') (id c') ) ) |
204 ≈⟨⟩ | 205 ≈⟨⟩ |
205 e' o (equalizer keqa o k keqa (id1 A c') ( f1=g1 (fe=ge eqa') (id1 A c') ) ) | 206 e' o (equalizer keqa o k keqa (id c') ( f1=g1 (fe=ge eqa') (id c') ) ) |
206 ≈⟨ cdr ( ek=h keqa ) ⟩ | 207 ≈⟨ cdr ( ek=h keqa ) ⟩ |
207 e' o id1 A c' | 208 e' o id c' |
208 ≈⟨ idR ⟩ | 209 ≈⟨ idR ⟩ |
209 e' | 210 e' |
210 ∎ | 211 ∎ |
211 | 212 |
212 -- e←e' e'←e = e | 213 -- e←e' e'←e e = e |
213 -- e'←e e←e = e' is enough for isomorphism but we want to prove l o r = id also. | 214 -- e'←e e←e e' = e' is enough for isomorphism but we can prove l o r = id also. |
214 | 215 |
215 c-iso→ : { c c' a b : Obj A } {f g : Hom A a b } → {e : Hom A c a } {e' : Hom A c' a} ( eqa : Equalizer A e f g) → ( eqa' : Equalizer A e' f g ) | 216 c-iso→ : { c c' a b : Obj A } {f g : Hom A a b } → {e : Hom A c a } {e' : Hom A c' a} ( eqa : Equalizer A e f g) → ( eqa' : Equalizer A e' f g ) |
216 → ( keqa : Equalizer A (k eqa' e (fe=ge eqa)) (A [ f o e' ]) (A [ g o e' ]) ) | 217 → ( keqa : Equalizer A (k eqa' e (fe=ge eqa)) (A [ f o e' ]) (A [ g o e' ]) ) |
217 → A [ A [ c-iso-l eqa eqa' keqa o c-iso-r eqa eqa' keqa ] ≈ id1 A c' ] | 218 → A [ A [ c-iso-l eqa eqa' keqa o c-iso-r eqa eqa' keqa ] ≈ id1 A c' ] |
218 c-iso→ {c} {c'} {a} {b} {f} {g} eqa eqa' keqa = let open ≈-Reasoning (A) in begin | 219 c-iso→ {c} {c'} {a} {b} {f} {g} eqa eqa' keqa = let open ≈-Reasoning (A) in begin |
219 c-iso-l eqa eqa' keqa o c-iso-r eqa eqa' keqa | 220 c-iso-l eqa eqa' keqa o c-iso-r eqa eqa' keqa |
220 ≈⟨⟩ | 221 ≈⟨⟩ |
221 equalizer keqa o k keqa (id1 A c') ( f1=g1 (fe=ge eqa') (id1 A c') ) | 222 equalizer keqa o k keqa (id c') ( f1=g1 (fe=ge eqa') (id c') ) |
222 ≈⟨ ek=h keqa ⟩ | 223 ≈⟨ ek=h keqa ⟩ |
223 id1 A c' | 224 id c' |
224 ∎ | 225 ∎ |
225 | 226 |
226 c-iso← : { c c' a b : Obj A } {f g : Hom A a b } → {e : Hom A c a } {e' : Hom A c' a} ( eqa : Equalizer A e f g) → ( eqa' : Equalizer A e' f g ) | 227 c-iso← : { c c' a b : Obj A } {f g : Hom A a b } → {e : Hom A c a } {e' : Hom A c' a} ( eqa : Equalizer A e f g) → ( eqa' : Equalizer A e' f g ) |
227 → ( keqa : Equalizer A (k eqa' e (fe=ge eqa )) (A [ f o e' ]) (A [ g o e' ]) ) | 228 → ( keqa : Equalizer A (k eqa' e (fe=ge eqa )) (A [ f o e' ]) (A [ g o e' ]) ) |
228 → ( keqa' : Equalizer A (k keqa (id1 A c') ( f1=g1 (fe=ge eqa') (id1 A c') )) (A [ f o e ]) (A [ g o e ]) ) | 229 → ( keqa' : Equalizer A (k keqa (id1 A c') ( f1=g1 (fe=ge eqa') (id1 A c') )) (A [ f o e ]) (A [ g o e ]) ) |
229 → A [ A [ c-iso-r eqa eqa' keqa o c-iso-l eqa eqa' keqa ] ≈ id1 A c ] | 230 → A [ A [ c-iso-r eqa eqa' keqa o c-iso-l eqa eqa' keqa ] ≈ id1 A c ] |
230 c-iso← {c} {c'} {a} {b} {f} {g} {e} {e'} eqa eqa' keqa keqa' = let open ≈-Reasoning (A) in begin | 231 c-iso← {c} {c'} {a} {b} {f} {g} {e} {e'} eqa eqa' keqa keqa' = let open ≈-Reasoning (A) in begin |
231 c-iso-r eqa eqa' keqa o c-iso-l eqa eqa' keqa | 232 c-iso-r eqa eqa' keqa o c-iso-l eqa eqa' keqa |
232 ≈⟨⟩ | 233 ≈⟨⟩ |
233 k keqa (id1 A c') ( f1=g1 (fe=ge eqa') (id1 A c') ) o k eqa' e (fe=ge eqa ) | 234 k keqa (id c') ( f1=g1 (fe=ge eqa') (id c') ) o k eqa' e (fe=ge eqa ) |
234 ≈⟨⟩ | 235 ≈⟨⟩ |
235 equalizer keqa' o k eqa' e (fe=ge eqa ) | 236 equalizer keqa' o k eqa' e (fe=ge eqa ) |
236 ≈⟨ cdr ( begin | 237 ≈⟨ cdr ( begin |
237 k eqa' e (fe=ge eqa ) | 238 k eqa' e (fe=ge eqa ) |
238 ≈⟨ uniqueness eqa' ( begin | 239 ≈⟨ uniqueness eqa' ( begin |
239 e' o k keqa' (id1 A c) (f1=g1 (fe=ge eqa) (id1 A c)) | 240 e' o k keqa' (id c) (f1=g1 (fe=ge eqa) (id c)) |
240 ≈↑⟨ car (e'←e eqa eqa' keqa ) ⟩ | 241 ≈↑⟨ car (e'←e eqa eqa' keqa ) ⟩ |
241 ( e o equalizer keqa' ) o k keqa' (id1 A c) (f1=g1 (fe=ge eqa) (id1 A c)) | 242 ( e o equalizer keqa' ) o k keqa' (id c) (f1=g1 (fe=ge eqa) (id c)) |
242 ≈↑⟨ assoc ⟩ | 243 ≈↑⟨ assoc ⟩ |
243 e o ( equalizer keqa' o k keqa' (id1 A c) (f1=g1 (fe=ge eqa) (id1 A c))) | 244 e o ( equalizer keqa' o k keqa' (id c) (f1=g1 (fe=ge eqa) (id c))) |
244 ≈⟨ cdr ( ek=h keqa' ) ⟩ | 245 ≈⟨ cdr ( ek=h keqa' ) ⟩ |
245 e o id1 A c | 246 e o id c |
246 ≈⟨ idR ⟩ | 247 ≈⟨ idR ⟩ |
247 e | 248 e |
248 ∎ )⟩ | 249 ∎ )⟩ |
249 k keqa' (id1 A c) ( f1=g1 (fe=ge eqa) (id1 A c) ) | 250 k keqa' (id c) ( f1=g1 (fe=ge eqa) (id c) ) |
250 ∎ )⟩ | 251 ∎ )⟩ |
251 equalizer keqa' o k keqa' (id1 A c) ( f1=g1 (fe=ge eqa) (id1 A c) ) ≈⟨ ek=h keqa' ⟩ | 252 equalizer keqa' o k keqa' (id c) ( f1=g1 (fe=ge eqa) (id c) ) ≈⟨ ek=h keqa' ⟩ |
252 id1 A c | 253 id c |
253 ∎ | 254 ∎ |
254 | 255 |
255 | 256 |
256 | 257 |
257 -------------------------------- | 258 -------------------------------- |
290 -- e o id1 ≈ e → k e ≈ id | 291 -- e o id1 ≈ e → k e ≈ id |
291 | 292 |
292 lemma-b3 : {a b d : Obj A} (f : Hom A a b ) { h : Hom A d a } → A [ A [ equalizer (eqa f f ) o k (eqa f f) (id1 A a) (f1=f1 f) ] ≈ id1 A a ] | 293 lemma-b3 : {a b d : Obj A} (f : Hom A a b ) { h : Hom A d a } → A [ A [ equalizer (eqa f f ) o k (eqa f f) (id1 A a) (f1=f1 f) ] ≈ id1 A a ] |
293 lemma-b3 {a} {b} {d} f {h} = let open ≈-Reasoning (A) in | 294 lemma-b3 {a} {b} {d} f {h} = let open ≈-Reasoning (A) in |
294 begin | 295 begin |
295 equalizer (eqa f f) o k (eqa f f) (id1 A a) (f1=f1 f) | 296 equalizer (eqa f f) o k (eqa f f) (id a) (f1=f1 f) |
296 ≈⟨ ek=h (eqa f f ) ⟩ | 297 ≈⟨ ek=h (eqa f f ) ⟩ |
297 id1 A a | 298 id a |
298 ∎ | 299 ∎ |
299 lemma-equ4 : {a b c d : Obj A} → (f : Hom A a b) → (g : Hom A a b ) → (h : Hom A d a ) → | 300 lemma-equ4 : {a b c d : Obj A} → (f : Hom A a b) → (g : Hom A a b ) → (h : Hom A d a ) → |
300 A [ A [ f o A [ h o equalizer (eqa (A [ f o h ]) (A [ g o h ])) ] ] ≈ A [ g o A [ h o equalizer (eqa (A [ f o h ]) (A [ g o h ])) ] ] ] | 301 A [ A [ f o A [ h o equalizer (eqa (A [ f o h ]) (A [ g o h ])) ] ] ≈ A [ g o A [ h o equalizer (eqa (A [ f o h ]) (A [ g o h ])) ] ] ] |
301 lemma-equ4 {a} {b} {c} {d} f g h = let open ≈-Reasoning (A) in | 302 lemma-equ4 {a} {b} {c} {d} f g h = let open ≈-Reasoning (A) in |
302 begin | 303 begin |
327 ∎ | 328 ∎ |
328 cong-δ1 : {a b c : Obj A} {e : Hom A c a } {f f' : Hom A a b} → A [ f ≈ f' ] → A [ k (eqa {a} {b} {c} f f {e} ) (id1 A a) (f1=f1 f) ≈ | 329 cong-δ1 : {a b c : Obj A} {e : Hom A c a } {f f' : Hom A a b} → A [ f ≈ f' ] → A [ k (eqa {a} {b} {c} f f {e} ) (id1 A a) (f1=f1 f) ≈ |
329 k (eqa {a} {b} {c} f' f' {e} ) (id1 A a) (f1=f1 f') ] | 330 k (eqa {a} {b} {c} f' f' {e} ) (id1 A a) (f1=f1 f') ] |
330 cong-δ1 {a} {b} {c} {e} {f} {f'} f=f' = let open ≈-Reasoning (A) in | 331 cong-δ1 {a} {b} {c} {e} {f} {f'} f=f' = let open ≈-Reasoning (A) in |
331 begin | 332 begin |
332 k (eqa {a} {b} {c} f f {e} ) (id1 A a) (f1=f1 f) | 333 k (eqa {a} {b} {c} f f {e} ) (id a) (f1=f1 f) |
333 ≈⟨ uniqueness (eqa f f) ( begin | 334 ≈⟨ uniqueness (eqa f f) ( begin |
334 e o k (eqa {a} {b} {c} f' f' {e} ) (id1 A a) (f1=f1 f') | 335 e o k (eqa {a} {b} {c} f' f' {e} ) (id a) (f1=f1 f') |
335 ≈⟨ ek=h (eqa {a} {b} {c} f' f' {e} ) ⟩ | 336 ≈⟨ ek=h (eqa {a} {b} {c} f' f' {e} ) ⟩ |
336 id1 A a | 337 id a |
337 ∎ )⟩ | 338 ∎ )⟩ |
338 k (eqa {a} {b} {c} f' f' {e} ) (id1 A a) (f1=f1 f') | 339 k (eqa {a} {b} {c} f' f' {e} ) (id a) (f1=f1 f') |
339 ∎ | 340 ∎ |
340 | 341 |
341 lemma-b2 : {d : Obj A} {h : Hom A d a} → A [ | 342 lemma-b2 : {d : Obj A} {h : Hom A d a} → A [ |
342 A [ equalizer (eqa f g) o k (eqa f g) (A [ h o equalizer (eqa (A [ f o h ]) (A [ g o h ])) ]) (lemma-equ4 {a} {b} {c} f g h) ] | 343 A [ equalizer (eqa f g) o k (eqa f g) (A [ h o equalizer (eqa (A [ f o h ]) (A [ g o h ])) ]) (lemma-equ4 {a} {b} {c} f g h) ] |
343 ≈ A [ h o equalizer (eqa (A [ f o h ]) (A [ g o h ])) ] ] | 344 ≈ A [ h o equalizer (eqa (A [ f o h ]) (A [ g o h ])) ] ] |
360 (lemma-equ4 {a} {b} {c} f g (( equalizer (eqa f g) o j ))) o | 361 (lemma-equ4 {a} {b} {c} f g (( equalizer (eqa f g) o j ))) o |
361 k (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) (id1 A d) (f1=f1 (( f o ( equalizer (eqa f g) o j ) ))) ) | 362 k (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) (id1 A d) (f1=f1 (( f o ( equalizer (eqa f g) o j ) ))) ) |
362 ≈⟨ car ((uniqueness (eqa f g) ( begin | 363 ≈⟨ car ((uniqueness (eqa f g) ( begin |
363 equalizer (eqa f g) o j | 364 equalizer (eqa f g) o j |
364 ≈↑⟨ idR ⟩ | 365 ≈↑⟨ idR ⟩ |
365 (equalizer (eqa f g) o j ) o id1 A d | 366 (equalizer (eqa f g) o j ) o id d |
366 ≈⟨⟩ -- here we decide e (fej) (gej)' is id1 A d | 367 ≈⟨⟩ -- here we decide e (fej) (gej)' is id d |
367 ((equalizer (eqa f g) o j) o equalizer (eqa (f o equalizer (eqa f g {e}) o j) (g o equalizer (eqa f g {e}) o j))) | 368 ((equalizer (eqa f g) o j) o equalizer (eqa (f o equalizer (eqa f g {e}) o j) (g o equalizer (eqa f g {e}) o j))) |
368 ∎ ))) ⟩ | 369 ∎ ))) ⟩ |
369 j o k (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) (id1 A d) (f1=f1 (( f o ( equalizer (eqa f g) o j ) ))) | 370 j o k (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) (id1 A d) (f1=f1 (( f o ( equalizer (eqa f g) o j ) ))) |
370 ≈⟨ cdr ((uniqueness (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) ( begin | 371 ≈⟨ cdr ((uniqueness (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) ( begin |
371 equalizer (eqa (f o equalizer (eqa f g {e} ) o j) (f o equalizer (eqa f g {e}) o j)) o id1 A d | 372 equalizer (eqa (f o equalizer (eqa f g {e} ) o j) (f o equalizer (eqa f g {e}) o j)) o id d |
372 ≈⟨ idR ⟩ | 373 ≈⟨ idR ⟩ |
373 equalizer (eqa (f o equalizer (eqa f g {e}) o j) (f o equalizer (eqa f g {e}) o j)) | 374 equalizer (eqa (f o equalizer (eqa f g {e}) o j) (f o equalizer (eqa f g {e}) o j)) |
374 ≈⟨⟩ -- here we decide e (fej) (fej)' is id1 A d | 375 ≈⟨⟩ -- here we decide e (fej) (fej)' is id d |
375 id1 A d | 376 id d |
376 ∎ ))) ⟩ | 377 ∎ ))) ⟩ |
377 j o id1 A d | 378 j o id d |
378 ≈⟨ idR ⟩ | 379 ≈⟨ idR ⟩ |
379 j | 380 j |
380 ∎ | 381 ∎ |
381 | 382 |
382 -------------------------------- | 383 -------------------------------- |
399 ek=h1 : {d : Obj A} → ∀ {h : Hom A d a} → {eq : A [ A [ f o h ] ≈ A [ g o h ] ] } → A [ A [ (α bur f g e) o k1 {d} h eq ] ≈ h ] | 400 ek=h1 : {d : Obj A} → ∀ {h : Hom A d a} → {eq : A [ A [ f o h ] ≈ A [ g o h ] ] } → A [ A [ (α bur f g e) o k1 {d} h eq ] ≈ h ] |
400 ek=h1 {d} {h} {eq} = let open ≈-Reasoning (A) in | 401 ek=h1 {d} {h} {eq} = let open ≈-Reasoning (A) in |
401 begin | 402 begin |
402 α bur f g e o k1 h eq | 403 α bur f g e o k1 h eq |
403 ≈⟨⟩ | 404 ≈⟨⟩ |
404 α bur f g e o ( γ bur {a} {b} {c} f g h o δ bur {d} {b} {d} (id1 A d) (f o h) ) | 405 α bur f g e o ( γ bur {a} {b} {c} f g h o δ bur {d} {b} {d} (id d) (f o h) ) |
405 ≈⟨ assoc ⟩ | 406 ≈⟨ assoc ⟩ |
406 ( α bur f g e o γ bur {a} {b} {c} f g h ) o δ bur {d} {b} {d} (id1 A d) (f o h) | 407 ( α bur f g e o γ bur {a} {b} {c} f g h ) o δ bur {d} {b} {d} (id d) (f o h) |
407 ≈⟨ car (b2 bur) ⟩ | 408 ≈⟨ car (b2 bur) ⟩ |
408 ( h o ( α bur ( f o h ) ( g o h ) (id1 A d))) o δ bur {d} {b} {d} (id1 A d) (f o h) | 409 ( h o ( α bur ( f o h ) ( g o h ) (id d))) o δ bur {d} {b} {d} (id d) (f o h) |
409 ≈↑⟨ assoc ⟩ | 410 ≈↑⟨ assoc ⟩ |
410 h o ((( α bur ( f o h ) ( g o h ) (id1 A d) )) o δ bur {d} {b} {d} (id1 A d) (f o h) ) | 411 h o ((( α bur ( f o h ) ( g o h ) (id d) )) o δ bur {d} {b} {d} (id d) (f o h) ) |
411 ≈↑⟨ cdr ( car ( cong-α bur eq)) ⟩ | 412 ≈↑⟨ cdr ( car ( cong-α bur eq)) ⟩ |
412 h o ((( α bur ( f o h ) ( f o h ) (id1 A d)))o δ bur {d} {b} {d} (id1 A d) (f o h) ) | 413 h o ((( α bur ( f o h ) ( f o h ) (id d)))o δ bur {d} {b} {d} (id d) (f o h) ) |
413 ≈⟨ cdr (b3 bur {d} {b} {d} (f o h) {id1 A d} ) ⟩ | 414 ≈⟨ cdr (b3 bur {d} {b} {d} (f o h) {id d} ) ⟩ |
414 h o id1 A d | 415 h o id d |
415 ≈⟨ idR ⟩ | 416 ≈⟨ idR ⟩ |
416 h | 417 h |
417 ∎ | 418 ∎ |
418 uniqueness1 : {d : Obj A} → ∀ {h : Hom A d a} → {eq : A [ A [ f o h ] ≈ A [ g o h ] ] } → {k' : Hom A d c } → | 419 uniqueness1 : {d : Obj A} → ∀ {h : Hom A d a} → {eq : A [ A [ f o h ] ≈ A [ g o h ] ] } → {k' : Hom A d c } → |
419 A [ A [ (α bur f g e) o k' ] ≈ h ] → A [ k1 {d} h eq ≈ k' ] | 420 A [ A [ (α bur f g e) o k' ] ≈ h ] → A [ k1 {d} h eq ≈ k' ] |
420 uniqueness1 {d} {h} {eq} {k'} ek=h = let open ≈-Reasoning (A) in | 421 uniqueness1 {d} {h} {eq} {k'} ek=h = let open ≈-Reasoning (A) in |
421 begin | 422 begin |
422 k1 {d} h eq | 423 k1 {d} h eq |
423 ≈⟨⟩ | 424 ≈⟨⟩ |
424 γ bur {a} {b} {c} f g h o δ bur {d} {b} {d} (id1 A d) (f o h) | 425 γ bur {a} {b} {c} f g h o δ bur {d} {b} {d} (id d) (f o h) |
425 ≈↑⟨ car (cong-γ bur {a} {b} {c} {d} ek=h ) ⟩ | 426 ≈↑⟨ car (cong-γ bur {a} {b} {c} {d} ek=h ) ⟩ |
426 γ bur f g (A [ α bur f g e o k' ]) o δ bur {d} {b} {d} (id1 A d) (f o h) | 427 γ bur f g (A [ α bur f g e o k' ]) o δ bur {d} {b} {d} (id d) (f o h) |
427 ≈↑⟨ cdr (cong-δ bur (resp ek=h refl-hom )) ⟩ | 428 ≈↑⟨ cdr (cong-δ bur (resp ek=h refl-hom )) ⟩ |
428 γ bur f g (A [ α bur f g e o k' ]) o δ bur {d} {b} {d} (id1 A d) ( f o ( α bur f g e o k') ) | 429 γ bur f g (A [ α bur f g e o k' ]) o δ bur {d} {b} {d} (id d) ( f o ( α bur f g e o k') ) |
429 ≈⟨ b4 bur ⟩ | 430 ≈⟨ b4 bur ⟩ |
430 k' | 431 k' |
431 ∎ | 432 ∎ |
432 | 433 |
433 | 434 |